2014
DOI: 10.1186/1471-230x-14-96
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of CNDP2 facilitates the proliferation of colon cancer

Abstract: BackgroundCytosolic nonspecific dipetidase (CN2) belongs to the family of M20 metallopeptidases. It was stated in previous articles that higher expression levels of CN2 were observed in renal cell carcinoma and breast cancer. Our study explored the correlation between CN2 and colon carcinogenesis.MethodsWe analysed the relationship between 183 patients clinicopathological characteristics and its CN2 expression. To detect the levels of CN2 in colon cancer cell lines and colon cancer tissues by western blot. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
10
2
Order By: Relevance
“…Many studies reported that the CNDP2 gene is misexpressed in different types of human cancers [ 2 , 6 11 ]. CNDP2 was also found to be involved in the regulation of the cell cycle in human cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reported that the CNDP2 gene is misexpressed in different types of human cancers [ 2 , 6 11 ]. CNDP2 was also found to be involved in the regulation of the cell cycle in human cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…CNDP2 was also found to be involved in the regulation of the cell cycle in human cancer cell lines. Specifically, CNDP2 overexpression in pancreatic cancer lines induced the accumulation of cells in the G0/G1 phase [ 6 ], whereas knockdown of CNDP2 in colon cancer cells blocked the cell cycle progression in the G2/M phase [ 11 ]. However, the molecular mechanisms underlying these effects have not been uncovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our transcriptional analysis reveals that cndp2 , which promotes cell proliferation, is more highly expressed in EB and apical-LB blastema populations. EGFR signaling is required for CNDP2 mediated proliferative activity [ 23 ] and is activated during regeneration [ 25 ]. Additionally, EGFR activity is induced by matrix metalloprotease activity in the regenerate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins identified in regions of gain included the established EGFR oncogene 21 , and candidates such as FOXK1, a forkhead transcription factor, and CNDP2, an activator of MAPK pathways. Increased expression of FOXK1 has been shown to promote CRC invasion and metastasis 22 , and up-regulation of CNDP2 to facilitate colon cancer proliferation 23 . In regions of loss, we identified several putative tumor suppressors, including MTHFD1, a 1-tetrahydrofolate synthase.…”
Section: Resultsmentioning
confidence: 99%